THE EFFECT OF EMPLOYEE ENGAGEMENT, WORK-LIFE BALANCE, AND WORK STRESS ON THE PRODUCTIVITY OF TOYOTA AUTO 2000 PLJU PALEMBANG EMPLOYEES - Dinda Dwi Deninta; Endah Dewi Purnamasari; Hamid Halin (Majapahit Journal of Islamic Finance and Management, 2026)
Employee productivity is an important factor in supporting company performance. This study aimed to analyze the effects of employee engagement, work-life balance, and work stress on employee productivity at Toyota Auto 2000 Plaju Paleimbang. This study employed a quantitative approach using questionnaire-based data collection distributed to employees. Data were analyzed using multiple linear regression with the assistance of SPSS veirsion 29. The results indicated that employee enggement and work-life balance had significant effects on employee productivity, while work stress did not have a significant effect. Simultaneously, employee engagement, work-life balance, and work stress influenced employee productivity. These findings indicate that improving employee engagement and maintaining work-life balance are essential to enhance employee productivity.